Die Bybel aan die universiteit en in die kerk - Pelser, G. M. M. (Hervormde teologiese studies, 1989)
The Bible at the university and in the church The question is posed as to the difference between the theological faculty and the church with regard to their respective approaches to and uses of the Bible. By means of a number of theses it is demonstrated that the respective approaches are actually quite different, resulting in a gap between faculty and church. Due to the scientific orientation and mission of the faculty, however, this gap is unavoidable and even necessary. Even so, this gap should not become of such a nature as to lead to estrangement. To counter this danger, resent insights and developments regarding the study of the Bible should be conveyed to the church, however in a constructive and comprehensible manner. To this venture faculty members and church ministers are equally responsible.